Phineas and Ferb. A very Perry Christmas [videorecording (DVD)] - Martella, Vincent, 1992-; Sangster, Thomas, 1990-; Tisdale, Ashley, 1985-; Rhea, Caroline, 1964-; O'Brien, Richard, 1942-; Baker, Dee Bradley (Disney DVD., 2010)
Phineas and Ferb and Perry the Platypus set out to thwart Dr. Doofenshmirtz's 'naughty' plot to ruin Christmas. Will they get everything wrapped up in time for Santa's flyby?